Abnormality and Stigmatization in Irvine Welsh's Trainspotting - Gutiérrez Sibaja, Alfonso 1985- (2017)
The article proposes a reading of Irvine Welsh's Trainspotting that parts from previous criticism that mostly concerned itself with debating asupposed glamorization of heroin abuse. Instead, this article focuses on the discursive mechanisms that classify the novel's characters as abnormal subjects with a created need to be disciplined and normalized. Specifically, it addresses Mark Renton's classification as abnormal in terms of ideology and drug addiction and how such labeling is related to stigmatization. Theoretical considerations regarding abnormality, stigmatization and the psychiatric discourse from the works of Michel Foucault, Erwin Goffman and Thomas Szasz are incorporated to the discussion of Mark Renton's mechanomorphist construction and its violent implications.
El artículo propone una lectura de la novela Trainspotting de Irvine Welsh que difiere de la crítica previa que mayormente se preocupó en debatir una supuesta glamorización del abuso de heroína. En vez, el artículo se enfoca en los mecanismos discursivos que clasifican a los personajes de la novela como sujetos anormales con una necesidad creada de ser disciplinados y normalizados. Específicamente se aborda la clasificación de Mark Renton como anormal en términos ideológicos y de adicción a las drogas y cómo tal etiqueta se relaciona a la estigmatización. Consideraciones teóricas de las obras de Michel Foucault, Erwin Goffman y Thomas Szasz sobre anormalidad, estigmatización y el discurso psiquiátrico son incorporadas a la discusión sobre la construcción mecanomorfizada de Mark Renton y sus violentas implicaciones.
En Revista Intersedes, vol. 18, no. 38 (marzo 2017)
Descripción basada en el contenido visto el 7 de febrero, 2025